Sense and Synchrony: Infant Communication and Musical Improvisation - Gratier, Maya; Magnier, Julien (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2012)
This paper explores the forms and functions of synchrony in two communicative contexts: jazz musicians’ performances and vocal communication between mothers and infants. We present the view that musical expression is first and foremost a form of communication, involving socially distributed practices that enable a coordination of ideas, intentions and meanings. We report on studies in developmental psychology that have highlighted infants’ early abilities to connect with others. Synchrony is quite possibly the most fundamental of these abilities, enabling flexible and affectionate social encounters. We go on to argue that synchrony grounds meaning and culture within interpersonal processes. Synchrony is, at heart, a semiotic process which can readily do without language.